Congenital mediastinal immature teratoma: a case report with autopsy findings - Aksoy, Figen; Şen, Cihat; Danişment, Nur (The Turkish Journal of Pediatrics, 2002)
A full-term newborn with karyotype 46, XX was delivered by cesarean section. She had severe respiratory distress and substernal retraction, and underwent emergency operation, but she died on the same day due to respiratory failure.The mother, 26-year-old prima gravida with no history of twinning, had been examined with ultrasonography at the 34th week of her pregnancy, which revealed a fetus with edema of head and neck region, a probable diaphragmatic hernia, polyhydramnios, and a large mediastinal mass with solid and multicystic parts with hypoplasia of the lungs.Autopsy revealed a 9 x 5 x 3 cm lobulated mediastinal mass with both solid and cystic areas, displacing the lungs and the heart postero-inferiorly and thymus anteriorly. The lungs were hypoplastic. Microscopically, the mass showed mature epithelial and mesenchymal tissues with primitive mesenchyme and immature neuroepithelium. All these findings led to the diagnosis of an immature teratoma.Mediastinal teratomas are rare and life-threatening, but early diagnosis and surgical intervention in a newborn with sufficient lung maturation may provide a long survival.
Keywords: mediastinal teratoma; extragonadal teratoma; immature teratoma